"Can you ask her about chronic illnesses, diabetes, and all that…?" Language Mediation and Patient Centered-Communication - Angelelli, Claudia Viviana (My University, 2018)
Outline of the talk: Medical communication and patient centredness Existing paradigms in medical and medical cross-cultural communication research Brief review of medical interpreting research Inter-disciplinarity in medical interpreting Two examples of language mediation in medical cross-cultural communication: at micro and macro level Conclusions Implications
Keywords: Traducción; Medical interpreting; Communication; Health